Pengaruh Variasi Menu, Cita Rasa Dan Harga Terhadap Keputusan Pembelian Pada Seiya Coffe Rantauprapat - Noni Ritonga Noni; Daslan Simanjuntak; Mhd Amin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of menu variation, taste, and price on customer satisfaction. The background of this research is based on the importance of understanding the factors that drive customer satisfaction in the increasingly competitive culinary industry. The research method employed a quantitative approach using multiple linear regression analysis with t-test. Data were collected from respondents who are customers at the research object and processed using statistical software.The results indicate that menu variation has a positive but insignificant effect on customer satisfaction. Taste also shows a positive yet insignificant effect on customer satisfaction. In contrast, price has a positive and significant effect on customer satisfaction, making it the dominant determining factor. Thus, a well-structured pricing strategy aligned with product value and quality becomes the primary focus in enhancing customer satisfaction, while menu variation and taste remain supportive factors.The implications of this study suggest that culinary business managers should prioritize balanced pricing strategies that reflect product quality, while simultaneously improving menu variation and taste to strengthen business attractiveness and differentiation.